MEDIATING ROLE OF CORPORATE GOVERNANCE ON CORPORATE SOCIAL RESPONSIBILITY AND FIRM VALUE OF PUBLICLY LISTED FOOD, BEVERAGE AND TOBACCO COMPANIES IN THE PHILIPPINES MODERATED BY FIRM SIZE AND AGE - Coleen D. de Leon (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
The study analyzed the relationship of Corporate Social Responsibility and Firm value of entities engaged in Food, Beverage and Tobacco industry in the Philippines, as mediated by Corporate Governance with firm’s size and age as moderator. A causal- explanatory research was utilized which used secondary data, particularly financial statements, Sustainability Reports and Annual Corporate Governance Reports of the twenty-four (24) publicly listed Food, Beverage, and Tobacco companies for the periods 2015 to 2019. Corporate Social Responsibility (CSR) was measured using CSR disclosure index as mapped in GRI Sector provided by the Global Reporting Initiative (GRI), Corporate Governance (CG) was measured through Corporate Governance Mechanism, while firm value was measured by Tobin’s Q. Thus, Structural Equation Model was used to identify the Corporate Social Responsibility, Corporate Governance and Firm Value relationship. Results disclosed that CSR has a significant and positive impact on firm value, while on the other hand, CG have been found out to have an insignificant and positive impact on Firm value. Similarly, CSR Index disclosures showed to have an insignificant and positive impact on CG. But, results unveil that Corporate Governance has no mediating effect on CSR-Firm value relationship, hence it is insignificant when used as mediator for CSR and firm value. Conversely, findings uncovered that firm age and size have a moderating effect on CSR-FV relationship.